Development and evaluation of the effectiveness of a mobile application module on medication adherence, medicine beliefs, health literacy and blood pressure for older adult stroke survivors in China - Wenjing, Cao (2024)
Improved stroke care has resulted in a significant 84% increase in global stroke survivors over the past two decades. As society ages, more research is needed for older stroke survivors. The COVID-19 pandemic has spurred the development of mobile health (mHealth). However, the data on the efficacy of the mHealth innovations in stroke is limited. This study aims to develop and evaluate the effectiveness of a mobile application for older adult stroke survivors on medication adherence, medicine beliefs, health literacy on stroke, and blood pressure (BP) in Chenzhou, China. The study was divided into three phases: identifying medication non-adherence and its factors (Phase 1), developing a mobile application (Phase 2), and evaluating its usability and effectiveness for older aadult stroke survivors (Phase 3). Phase 1 was a cross-sectional study that involved 402 older adult stroke survivors from three tertiary hospitals in China. In Phase 2, a mobile application intervention module (e-MAIMOASS) was developed and validated. In phase 3, 82 older adult stroke survivors were randomly allocated to either the e-MAIMOASS group (n=41) or the control group (n=41). All subjects had to report medication adherence and BP at baseline, 1-month, and 3-month follow-ups. Medicine beliefs and health literacy were assessed at baseline and three months post-intervention. In Phase 1, 61.4% of participants exhibited medication non-adherence. Compared to individuals with primary education or less, those with a junior school education level had their odds of medication non-adherence decrease by 0.450 times, while those with a senior secondary or junior college education level experienced a decrease of 0.440 times. The higher the number of prescription medications an individual takes per day, the greater the likelihood of medication non-adherence (OR = 1.315). A significant association was found between medication non-adherence and health literacy (β = -0.059), BMQ Specific-Necessity score (β = -0.130), and BMQ Specific-Concerns score (OR=1.127). In Phase 2, a validated e-MAIMOASS comprising five core components received positive feedback and user satisfaction from Alpha and Beta testing. In Phase 3, older adult stroke survivors with the intervention exhibited enhanced medication adherence (p<0.001), significantly lower systolic BP (SBP) (p=0.009), improved health literacy (p=0.024), and better BMQ necessity scores (p=0.002) compared to the control group. The usability score for e-MAIMOASS was recorded with an average of 70.36 ± 7.05, surpassing the System Usability Scale (SUS) threshold of 68. In conclusion, the e-MAIMOASS effectively improved older adult stroke survivors' medication adherence, medicine beliefs, health literacy on stroke, and BP. However, more studies need to be conducted to improve the outcomes of this promising intervention.